Fingerprick versus oral swab: Acceptability of blood-based testing increases if other STIs can be detected - Balán, Ivan (AIDS Behav, 2017)
Self-testing has untapped potential as a strategy to improve access to HIV testing and to increase testing frequency. User acceptability of self-administered oral swab HIV tests is consistently high in both hypothetical and actual-use studies. We explored preferences for oral versus fingerprick HIV self-tests among men who have sex with men (MSM) with a high risk profile. Participants indicated greater likelihood of using an oral swab over a blood-based test, notwithstanding lower price or quicker results from the latter. However, the likelihood of using an HIV fingerprick test substantially increased if it also offered information on other sexually transmitted infections.